Starting Your Own : Wine Business / W. C. Morris - Morris, W. C.
You have been making wine in your base ment for several years and routinely receive accolades on how good your homemade wine tastes. Now you are trying to decide if you should start your own vineyard and build a commercial winery. What are the factors that you should consider in starting a winery and a vine yard? There are many aspects to consider in starting a winery. One of the ﬁrst considerations should be where to get grapes and what kind of wine to make. You also need to familiarize yourself with the various regulations and governing bodies that regulate the industry.